Educational leadership: perspectives, management and challenges - Wang, Viktor (New York: Nova Science Publishers, 2020)
'All 21st century leaders must be forward looking and have a well developed capability to anticipate or envision the future. They will need to have wisdom and the ability to think outside the box and possess the ability to turn crises and threats into opportunities. Thus, the topic of educational leadership remains a hot topic for debate and development. This book provides a strong base of reliable, verifiable knowledge needed to foster development of educational leadership capabilities across a diversity of domains and it shares a diversity of perspectives, experiences, theories and philosophies related to educational leadership across all levels of education. Educational Leadership: Perspectives, Management and Challenges is a leading edge research publication that examines leadership theories and practices that educational institutions must employ to be proactive, visionary, and ethically sound. The publication covers the importance of educational leadership as well as the foundation for developing frameworks in which to ground the presence of leadership in education. While featuring a wide range of topics such as principals' leadership styles, the significance of agility in the digital age, and sustained competitiveness, this book is ideal for librarians, academicians, administrators, researchers, education professionals, policymakers, and students'--
Andragogy, leadership and learning organizations -- Where have all the leaders gone? Leading in the Anthropocene -- Quebec: Past, present and future perspectives in educational leadership training -- Nexus between principal leadership and student learning -- Leader-making practices -- Developing the next generation of leaders -- The political economy of academic leadership -- Values based educational leadership -- Digital education leadership development for strategic change in higher education -- Agility at the fulcrum of leadership in the digital age -- Toward a process paradigm of educational leadership -- Understanding leadership within higher education: How community resilience strengthens humanics across team collaborations -- What is the propinquity between unlearning and organizational innovation capabilities? -- Using coordination theory to investigate the relationship between educational leadership, interdependence, and mentoring provided -- Central Florida Service Collective: Connecting national service to higher education to strengthen communities -- Higher education disruption: How transformational academic leaders can be the exceptional change agents needed in the future of higher education -- Universities, learning organizations and educational leadership.
Includes bibliographical references and index.
Keywords: Educational leadership; School management and organization; School improvement programs